Implication of Catchment Morphometric on Small River Discharge of Upper Citarik River, West Java - Edi Tri Haryanto; Emi Sukiyah; Pradnya Paramarta Raditya Rendra; Hendarmawan Hendarmawan; Suratman Suratman (Indonesian Journal of Geography, 2019)
Upper Citarik River is the Inter Mountainous Valley of Volcanic Denudational Landform in the eastern part of Bandung basin, West-Java. The research area compounds of several degraded small catchments with very low water flow in dry season. This research aims  to understand the implications of morphometric characteristics (Slope, Cr, Dd, Hi) on average river flow discharge of small sub-catchments of Upper Citarik River. Discharge data collected based on measurements, while catchments morphometric identified and analyzed based on topographic map using GIS techniques.  Correlation graphs were used to understand the relationship among the morphometric parameter and the average river flow discharges. The result were as follow  the steeper the slope, the more elongated the shape of catchment, the more distant was the river density,  meaning the more younger the erosion cycle of the landform.  The younger the erosion cycle of the landform, the smaller was the average river discharge per areal unit of catchments.